HYPNOTHERAPY FOR CHILD PERPETRATORS IN CRIMINAL ACTS - Ratna Widianing Putri (Cepalo, 2022)
Social changes in the era of technological advances open up great opportunities for lousy content for children's education, such as pornography, violence, bullying, murder, and others. This can cause a child's subconscious mind to learn and observe the environment so that it is embedded as values and mindsets and ultimately triggers children to commit criminal acts. Developing a more comprehensive coaching model to change behavior and thought patterns by accessing the subconscious mind through hypnotherapy techniques is not enough based on these conditions. The research method in this article is exercised through a literature study using primary and secondary data. The purpose of this research the article is to inform a model from the guide for child perpetrators of criminal activity through that Addition from a hypnotherapy program and to inform a model of guidance at LPKA for child perpetrators of criminal acts through the Addition of a hypnotherapy program. The theoretical approaches to analyze this article are differential association theory and coaching theory. The research method involves in-depth interviews with informants and a literature study using secondary data from decisions, journals, books, previous research, and articles.